P26 Impact of hiatus hernia in hypersensitivity pneumonitis – experience at a tertiary centre. (11th November 2022) - Heriot, DA; Stock, CJW; Mumtaz, Z; Jenkins, RG; Chua, F; Molyneaux, PL; Devaraj, A; Kouranos, V; Wells, AU; Renzoni, EA; Padley, SPG; Desai, SR; et al.
Abstract : Introduction: Hiatus hernias (HH) are present in 40% of patients with idiopathic pulmonary fibrosis (IPF) and are associated with more rapid lung function decline and increased mortality. The possibility of a similar impact of HH in patients with hypersensitivity pneumonitis (HP) has not been previously investigated. This study explored the prevalence and prognostic impact of HH in HP. Methods: CT scans and clinical data in consecutive patients with HP were retrospectively evaluated. CT studies were evaluated for the presence and size of HH (grades 0/1 [none/smallest] to 4 [largest]) by two consultant observers; a control group of patients without interstitial lung disease (ILD) was also evaluated. The pattern and extent of fibrosis (%), if present, were recorded; CT features suggesting aspiration (consolidation, bronchial wall thickening, tree-in-bud pattern) were noted. The primary outcome measure was the impact of HH on survival. Secondary analyses included impact on lung function trajectory using mixed effects modelling. Results: We studied 141 patients with HP (F=78(55%); mean age=64.2±9.6 yrs) and 175 controls (F=100(57%), mean age=60.7±13.1 yrs). The prevalence of HH was higher in patients with HP than controls (60% vs 25%; p<0.001) and there were more HH graded 2–4 than in controls (32% vs 3% respectively; p<0.001). There was no association between presence or size of HH and lung function decline, fibrosis extent on CT, body mass index, or mortality. A sub-group with a usual interstitial pneumonia pattern of fibrosis (n=23) had a trend towards worse survival associated with the presence of HH (HR=2.86, 95% CI: 0.91–8.97, p=0.072). CT signs suggesting aspiration were more frequent in patients with larger HH (13% of patients with HH grade 2–4 patients had consolidation vs. 3% of grade 0–1; p=0.021), with an exposure-response relationship. Conclusions: HH is more prevalent in patients with HP than IPF or in a control population without ILD. While HH is not associated with worse outcomes, the high prevalence and linkage between larger HH and CT signs of aspiration may provide insights into disease pathogenesis. Alongside genetic susceptibility and antigen exposure, HH and reflux may play a role in the development and propagation of HP.